Bond market co-movements, expected inflation and the equilibrium real exchange rate - Corrado Macchiarelli (European Central Bank (ECB), 2011)
Since the end of the fixed rates in 1973 and after the EMS sterling dismissal in 1992, the value of the pound has undergone large cyclical fluctuations on average. Of particular interest to policy makers is the understanding of whether such movements are consistent with the lack or not of a correction mechanism to some long-run equilibrium. The purpose of the present study is to understand those dynamics, how the external value of the British sterling relative to the USD evolved during the recent floating experiences, and what have been the driving forces. In this paper we assume the real exchange rate to be determined by forces relating to the goods and capital market in a general equilibrium framework. This entails testing the purchasing power parity and the uncovered interest parity together. Our findings have two important implications, both for monetary policy. First, we show that some of the observed changes in the real exchange rates can not be solely attributed to changes in inflation rates, but, possibly, also to investors' behavior. Secondly, we show that the special US dollar status of World reserve currency results into a weaker behavior of the US bond rate on international markets.
Keywords: E31; E43; E44; F31; C58; 330; international parity conditions; PPP; RIP; UIP